2020
DOI: 10.31015/jaefs.2020.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on germination and seedling growth of wheat cultivars under salt stress regimes

Abstract: Salinity interferes with germination and hampers the growth of wheat especially at seedling stage which necessitates determining of salt tolerant cultivars. Based upon the current situation a controlled experiment was carried out at the Laboratory of Horticulture, Faculty of Agriculture, Cukurova University, Turkey to comparatively evaluate wheat varieties response to imposed salt stress. Germination and seedling growth properties under salt stress were taken as response variables. The seeds of five bread whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…The increase in salt stress resulted in significant reductions in the root length of both genotypes. In accordance with our findings, many researchers have stated that increasing levels of salinity stress resulted in a higher degree of adverse effects on the root length of many field crops (Yildirim et al, 2015;Iyem et al, 2020;Kizilgeci et al, 2020). Additionally, it was also inferred that SA applications up to 100 mM salinity level imparted a positive effect on the root length of the DZ17-1 genotype.…”
Section: Root Lengthsupporting
confidence: 92%
See 4 more Smart Citations
“…The increase in salt stress resulted in significant reductions in the root length of both genotypes. In accordance with our findings, many researchers have stated that increasing levels of salinity stress resulted in a higher degree of adverse effects on the root length of many field crops (Yildirim et al, 2015;Iyem et al, 2020;Kizilgeci et al, 2020). Additionally, it was also inferred that SA applications up to 100 mM salinity level imparted a positive effect on the root length of the DZ17-1 genotype.…”
Section: Root Lengthsupporting
confidence: 92%
“…The increasing level of salinity caused a proportionate decrease in the dry weight of the seedlings. These results are in complete agreement with those of Iyem et al (2020) who reported that salinity significantly enhanced the dry weight of wheat owing to increased biosynthesis of antioxidants and various enzymes which ameliorated the adverse effects of salinity and ultimately seedling growth was promoted which resulted in the maximized seedling weight of wheat. The effects of SA acid application on seedling dry weight under salt stress conditions were similar.…”
Section: Seedling Dry Weightsupporting
confidence: 92%
See 3 more Smart Citations